Impact of increasing one-carbon metabolites on traumatic brain injury outcome using pre-clinical models - Sanika M Joshi; Theresa Currier Thomas; Nafisa M Jadavji (Neural Regeneration Research, 2024)
Traumatic brain injury is a major cause of death and disability worldwide, affecting over 69 million individuals yearly. One-carbon metabolism has been shown to have beneficial effects after brain damage, such as ischemic stroke. However, whether increasing one-carbon metabolite vitamins impacts traumatic brain injury outcomes in patients requires more investigation. The aim of this review is to evaluate how one-carbon metabolites impact outcomes after the onset of traumatic brain injury. PubMed, Web of Science, and Google Scholar databases were searched for studies that examined the impact of B-vitamin supplementation on traumatic brain injury outcomes. The search terms included combinations of the following words: traumatic brain injury, dietary supplementation, one-carbon metabolism, and B-vitamins. The focus of each literature search was basic science data. The year of publication in the literature searches was not limited. Our analysis of the literature has shown that dietary supplementation of B-vitamins has significantly improved the functional and behavioral recovery of animals with traumatic brain injury compared to controls. However, this improvement is dosage-dependent and is contingent upon the onset of supplementation and whether there is a sustained or continuous delivery of vitamin supplementation post-traumatic brain injury. The details of supplementation post-traumatic brain injury need to be further investigated. Overall, we conclude that B-vitamin supplementation improves behavioral outcomes and reduces cognitive impairment post-traumatic brain injury in animal model systems. Further investigation in a clinical setting should be strongly considered in conjunction with current medical treatments for traumatic brain injury-affected individuals.